Pelatihan untuk Meningkatkan Keterampilan dan Kemandirian Generasi Penerus Bangsa Pada SMK Bina Industri - Supartono; Salsabila, Lubna; Kamiliya, Nada; Nurkholifah, Ridha; Wahyuningsih, Sri; Agustina, Arindra Nurlaila; Sarah, Dede; Septian, Rudi; Utami, Rina Latifah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This Real Work Lecture (KKN) activity aims to improve the skills and independence of the nation's next generation at SMK Bina Industri. This activity is carried out by holding a seminar on successful strategies for entering the world of work. This seminar was attended by 50 students of SMK Bina Industri and 1 resource person from the Jatiwangi KKN team at Pelita Bangsa University using the observation method at the school. The evaluation results show that this seminar can improve students' knowledge and skills in entering the world of work. The research results show that synergy between study programs can increase skills and capacity for successful work strategies, so that it can increase entrepreneurial independence and sustainable development in villages. Therefore, this research recommends that study programs can increase synergy between study programs in developing villages towards entrepreneurial independence and sustainable development.